Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058